Analyses of the relationship between drought occurrences and their causal factors in Tigray Region, Northern Ethiopia. Issue 1 (1st January 2020) - Tefera, A.S.; Ayoade, J.O.; Bello, N.J.
Abstract: Drought is controlled and enhanced by changes in the local and global climate factors. The changes in the global factors mainly occur on the vast oceanic surfaces, while the changes in the local factors occur in the area of drought influence. In order to skilfully forecast and monitor drought occurrences, it is crucial that the specific causal factors be identified and their links studied. Based on this concept, this study tried to establish a relationship between the drought occurrences in Tigray region and the climate factors at the local and global scale. Monthly gridded Climatic Research Unit (CRU) Time-series (TS) data version 4.01 was used to calculate the Standardized Precipitation and Evapotranspiration Index (SPEI). As potential global causal factors, SOI (Southern Oscillation Index), Sea Surface Temperature Anomalies (SSTAs) of the tropical oceanic surfaces, the Red Sea and Nino 3.4 regions were obtained from various sources. Vegetation cover and albedo data were also considered as local drought causal factors. The analyses results show that the zero-time-lag SSTA in the tropical Indian Ocean was identified as statistically significant (p < 0.01) drought influencing factor accounting for 5.8% and 8% of the variations in SPEI, at 1-month and 6-month time scales respectively. At 12-month time scale, however, the SSTAs in the tropical Indian Ocean, tropical Atlantic Ocean, tropical Pacific Ocean, the Red Sea and Nino 3.4 regions were designated as drought influencing factors. Differently, at 24-month time scale, SOI was also identified as drought influencing factor in addition to the SSTAs in the tropical Indian Ocean, tropical Pacific Ocean and the Red Sea region. In general, the findings revealed the variability in the number and type of causal factors based on time scale and time-lag. Nevertheless, the ability of the identified factors to explain the variation in SPEI remained small at all timescales investigated. This, therefore, indicates the need for further investigation on other drought causal factors in the study area.